THE EFFECT OF LOCAL OWN-SOURCE REVENUE ON LOCAL EXPENDITURE IN THE PROVINCE OF NORTH SUMATRA - Fachri Ikhram; Yunita Sari Roni (International Journal of Management, Economic and Accounting, 2025)
Regional Original Revenue (PAD) and Regional Expenditure are two important components in the Regional Budget (APBD) that have a reciprocal relationship. PAD is the main source of financing local expenditure, and the amount of PAD affects the level and type of local expenditure that can be made by local governments. However, in practice, there are several problems related to the influence of PAD on local expenditure: Excessive Dependence on PAD. Many regions in North Sumatra are still overly dependent on own-source revenue to finance local expenditure. This research approach is to use the Causal method. The research was conducted at the Central Bureau of Statistics, starting from May 2024. For more details, it can be seen from the following table description. Conclusion PAD significantly has a positive and significant effect, this is in line with research conducted by Pasarribu (2022) with the title The Effect of Regional Original Revenue on Regional Expenditure in Toba Samosir Regency.